La propuesta de directiva europea sobre el trabajo en plataformas digitales: Una perspectiva comparada = The regulation of working conditions in platform work and the EU Proposal Directive : A comparative analysis - Facciotti, Paolo (Vergentis, 2023)
The appearance of new technologies has had its impact on the new economy, and this has been also translated into a change in the labor relations. This paper analyzes the legislation that regulates the employment relationships of people working through digital labor platforms, focusing on food delivery workers, or also called "riders." On the one hand, the article analyzes different decisions and judicial rulings that allow progress in Spanish legislation in this area, giving birth to the "Rider Law", and on the other hand, analyzes the European proposal for a Directive on improving working conditions in platform work, also carrying out a comparative study between different legislations, highlighting the comparison with Italian legislation and analyzing the impact on the different legal systems of the possible transposition of this proposal for a directive